Rancang bangun dan pengujian sistem penjatah pada prototipe mesin pemipih emping beras - Suhendra Suhendra; Feby Nopriandy (TURBO [Tulisan Riset Berbasis Online], 2022)
Rice quaker is a traditional culinary still made manually. Efforts to improve the rice quaker production process have been carried out by build a prototype of rice quaker flattening machine. The machine has a weakness because it is not equipped with a rationing system that can adjust the flattening capacity. Based on these problems, further research was carried out with designing and testing the rationing system on the rice quaker flattening machine. The stages of the research are to design the shape, create a rationing system, conduct testing and analyze the results. The independent variables of the study were the number of spaces and the rotational speed of the rationer. The independent variables of the study were the capacity and level of material damage. The rationing system has dimensions of 30 cm x 20 cm x 95.5 cm, weight 12 kg, use pulley and belt transmission system, with a 24V 120 Watt DC motor drive system. The test results at the rotation speed 50-300 rpm did not find any damage to the test material. The damage was found when the rotational speed reached 350 rpm. The rationing system prioritizes the stability of the output material over the capacity. Based on the test results, the recommended rotational speed of the rationing system is 200-300 rpm with the recommended number of rationing chambers of 10. At this recommendation value, the capacity obtained is 83,61 – 92,83 kg/hour.